1978
DOI: 10.1111/j.1365-2125.1978.tb04605.x
|View full text |Cite
|
Sign up to set email alerts
|

Disopyramide serum and pharmacologic effect kinetics applied to the assessment of bioavailability.

Abstract: I Serum, urine and pharmacologic effect (prolongation of the QT interval) kinetics of the antiarrhythmic disopyramide have been investigated in eight volunteers after intravenous administration (2 mg/kg) and oral administration (300 mg) of the two commercially available preparations, Rythmodan (Roussel Laboratories) and Norpace (Searle Laboratories). 2 An open one compartment body model adequately described the kinetics of disopyramide in serum and urine. 3 After intravenous administration, the following avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…However, it has been shown that drug distribution is extremely rapid (Hinderling & Garrett, 1976) (Bryson et al, 1978;: observation is consistent with s( (Rango et al, 1976 Karim, 1975 …”
Section: Pharmacokinetic Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…However, it has been shown that drug distribution is extremely rapid (Hinderling & Garrett, 1976) (Bryson et al, 1978;: observation is consistent with s( (Rango et al, 1976 Karim, 1975 …”
Section: Pharmacokinetic Analysissupporting
confidence: 53%
“…This employed a Perkin Elmer F33 gas liquid chromatograph equipped with a Perkin Elmer nitrogen/phosphorus detector. Details of the extraction procedure, operating conditions, and assay precision have been published previously (Bryson et al, 1978).…”
Section: Drug Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Ten cardiac cycles were measured and averaged for each determination of systolic time intervals and for each ECG. The QS2 interval, left ventricular ejection time (LVET) and the QT interval on the ECG were corrected for heart rate using regression equations derived previously (Burgess et al, 1978;Bryson et al, 1978): QS2 index = QS2 (in ms) + (1.2 x heart rate); LVET index = LVET + (1.1 x heart rate); pre-ejection period (PEP) requires no correction for heart rate; QT index = QT + (1.7 x heart rate) and corrected QT interval 93-methyl carbacyclin and epoprostenol in man…”
Section: Healthy Volunteer Studymentioning
confidence: 99%
“…A recent paper on the assessment of disopyramide bioavailability (Bryson, Whiting & Lawrence, 1978) presented pharmacodynamic data which suggested that prolongation of the QT interval after oral administration was directly proportional to the plasma disopyramide concentration. Effect and concentration were plotted against each other on linear axes and the degree of hysteresis, i.e.…”
Section: Introductionmentioning
confidence: 99%